The Legal Category of Authenticity. An Attempt at Definition - O. A. Krestovnikov (Теория и практика судебной экспертизы)
In law enforcement and in scientific research the category of authenticity is used both for theoretical conceptualization and in practical contexts. However, the lack of a universally accepteddefinition undermines the utility of this concept in the production of evidence, as well as development of scientific resources and databases. The paper offers an initial attempt to define authenticity in the context of law enforcement and examines the most significant tools of authenticity analysis and verification: the civil law notary authentication and forensic identification